OC-096 The delivery of high-risk emergency general surgery across the dr foster global comparators network: an examination of international outcomes. (22nd June 2015) - Chana, P; Casey, N; Chang, D; Joy, M; Burns, E; Arora, S; Darzi, A; Peden, C; Faiz, O
Abstract : Introduction: The Dr Foster Global Comparators Network (GC) aims to improve quality in healthcare by promoting inter-hospital collaboration through sharing of outcome data and benchmarking standards. This study aims to utilise the GC database to establish whether geographical differences in outcomes exist following high-risk emergency general surgery (EGS) admissions, whilst determining if structural differences between healthcare systems can be linked to high-quality care. Method: Discharge data for a cohort of EGS patients were collated using a pre-determined protocol. Hierarchical logistic regression analysis was performed to examine geographical and structural differences between GC hospitals. Results: 69, 490 patients, admitted to 23 centres across Australia, England and the USA with high-risk EGS diagnoses from 2007–2012 were identified. Outcomes including: seven/thirty-day mortality, readmission and length of stay were all superior in the USA. 19, 082 patients (27%) underwent emergency abdominal surgery. No geographical differences in mortality were seen at seven-days in this subgroup. Thirty-day mortality (OR = 1.47) readmission (OR = 1.42) and length of stay (OR = 1.98) were all worse in the UK. Across this cohort, patient factors, (age, pathology and co-morbidity) were significantly associated with worse outcome as were structural factors including: low ITU bed ratios, high unit volume and inter-hospital transfers. Having dedicated EGS teams cleared of elective commitments with formalised handover of patients was associated with shorter length of stay. Conclusion: Post-operative outcomes were similar at seven but not at thirty-days. This may be attributable to better infrastructure and resource allocation towards EGS in the US. The costs associated with this healthcare gain were not measured. Disclosure of interest: None Declared.